IDENTIFICATION OF STUDENT'S MISCONCEPTIONS ON STRAIGHT MOTION MATERIALS USING FOUR-TIER DIAGNOSTIC TEST AND CERTAINTY OF RESPONSE INDEX (CRI) - Izzati Salsabilla Madina; Ratnawulan R; Silvi Yulia Sari; Putri Dwi Sundari; Tantri Mayasari (Universitas Negeri Padang, 2022)
Student’s understanding that is not in accordance with scientific concepts becomes an obstruction in the process of studying and effect on the result of studying itself. Therefore, an effort is needed to fix and find out the students’ misconception. Therefore, this study aims to identify the level of student’s concept understanding and misconceptions on the material of straight motion at SMAN 11 Padang, SMAN 13 Padang, and SMAN 16 Padang. This study is the descriptive research by using quantitative approach. The instrument used is the Four-Tier Multiple Choice Test with a Certainty of Response Index (CRI) scale. The study population was all students of class X at SMAN 11 Padang, SMAN 13 Padang, and SMAN 16 Padang in the academic year 2021/2022. The simple random sampling technique is used in this study as much as 20% of the total population, so the number of samples in this study was 135 students. The results indicate that the level of student’s concept understanding on the material of straight motion at SMAN 11 Padang, SMAN 13 Padang, and SMAN 16 Padang was in the low category with the level of misconceptions in the medium category. At SMAN 11 Padang the percentage of understanding concepts is 14.1% and misconceptions is 44.9%. At SMAN 13 Padang the percentage of understanding concepts is 13.2% and misconceptions is 47.7%. And at SMAN 16 Padang the percentage of understanding concepts is 12.6% and misconceptions is 55.7%. It can be stated that the level of student’s concept understanding is more dominant in the category of misconceptions in straight motion material.